2008
DOI: 10.1002/marc.200800325
|View full text |Cite
|
Sign up to set email alerts
|

Improved PEDOT Conductivity via Suppression of Crystallite Formation in Fe(III) Tosylate During Vapor Phase Polymerization

Abstract: Vapor phase polymerization was used to synthesize high conductivity poly(3,4‐ethylenedioxyphenylene) (PEDOT). The monomer is presented to an oxidant‐rich substrate in vapor form and even for short polymerization times, 10–30 min, Fe(III) tosylate has a propensity for water absorption leading to crystal formation. Poor oxidant treatment before polymerization or high humidity during polymerization can create holes in the PEDOT film decreasing its conductivity. The addition of an amphiphilic copolymer poly(ethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(72 citation statements)
references
References 23 publications
0
70
0
2
Order By: Relevance
“…18 Electrochemical polymerization only allows the coating of conductive substrates and can produce nonuniform films for larger areas. 19 VPP offers a viable alternative to other methods of preparing highly conductive PEDOT films. A conductive polymer film is formed by a chemical reaction between an oxidant and EDOT obtained from vapor phase.…”
mentioning
confidence: 99%
“…18 Electrochemical polymerization only allows the coating of conductive substrates and can produce nonuniform films for larger areas. 19 VPP offers a viable alternative to other methods of preparing highly conductive PEDOT films. A conductive polymer film is formed by a chemical reaction between an oxidant and EDOT obtained from vapor phase.…”
mentioning
confidence: 99%
“…Another study investigating both the effects of humidity and PEG-ran-PPG as an additive found an optimal relative humidity of 35%, yielding the highest conductivity film, as shown in Figure 12. 83 A similar dependence on the presence of water vapor during polymerization was seen in depositing PPy. 86 Fabretto et al suggest that the water is acting as an effective proton scavenger allowing polymerization to proceed.…”
Section: Reviewmentioning
confidence: 58%
“…55,82 In addition to controlling the humidity in the VPP chamber, incorporation of a surfactant such as poly(ethylene glycol)-ran-poly(propylene glycol) (PEG-ran-PPG) to the oxidant solution also inhibits the adverse effects of water absorption and prevents the oxidant from forming crystallite domains during the VPP process resulting in a significant increase in the conductivity from 84 S cm À1 to 528 S cm À1 . 83,84 It is believed that PEG-ran-PPG co-ordinates to the Fe 3þ ions in the oxidant iron(III) tosylate and reduces the effective reactivity of the oxidant which reduces the rate of polymerization leading to increased conductivity as shown in Figure 11. 84 Further studies revealed that the surfactant can potentially replace the weak bases such as pyridine and imidazole in reducing the apparent reactivity of the oxidant, thus eliminating the problems associated with volatility of low molecular weight organic bases.…”
Section: Reviewmentioning
confidence: 99%
“…The evaporation of residual butanol from the dot exposes the hygroscopic Fe(III) tosylate which, on cooling, absorbs water from the atmosphere to form large (400−600 nm high) crystals. 11 A dot of oxidant ink which has been exposed to EDOT monomer in the VPP chamber ( Figure 3G−I) exhibits a nodular morphology and little, if any, crystallization. In this case the oxidant has polymerized the monomer and the tosylate anion has become incorporated in the resulting PEDOT as dopant.…”
Section: ■ Results and Discussionmentioning
confidence: 99%